Anda di halaman 1dari 3

# Binomial Theorem

The coefficients of the expansions of a binomial are arranged in an array. This array is called
Pascals triangle. It can be written as

Index Coefficient(s)
0
0
0
( 1)
C
=

1
1 1
0 1
( 1) ( 1)
C C
= =

2
2 2 2
0 1 2
( ) ( 1) ( 1) 2
C C C
= = =

3
3 3 3 3
0 1 2 3
( ) ( ) ( 1) ( 1) 3 3
C C C C
= = = =

4
4 4 4 4 4
0 1 2 3 4
( ) ( ) ( 1) ( 1) ( ) 4 6 4
C C C C C
= = = = =

5
5 5 5 5 5 5
0 1 2 3 4 5
( ) ( 10) ( ) ( 1) ( 10) ( 1) 5 5
C C C C C C
= = = = = =

The expansion of a binomial for any positive integral n is given by the Binomial Theorem,
which is as follows:
1 2 2 1
0 1 2 1
( ) C C C ... C C
n n n n n n n n n n n
n n
a b a a b a b a b b

+ = + + + + +

Observations made using the binomial theorem:
The notation
0
C
n
n n k k
k
k
a b

stands for
0 1 1
0 1
C C ... C ... C
n n n n n n r r n n n n
r n
a b a b a b a b

+ + + + +
Where, b
0
= 1 =
n n
a

Hence, the binomial theorem can also be stated as:
0
( ) C
n
n n n k k
k
k
a b a b

=
+ =

The coefficients of C
n
k
occurring in the binomial theorem are known as binomial
coefficients.
In the expansion of (a + b)
n
, there are (n + 1) terms, i.e., one more than the index.
Example: The number of terms in the expansion of (5x + 7y)
9
is 9 + 1 = 10
In the successive terms of the expansion of (a + b)
n
, the index of a goes on decreasing by
unity, starting with n in the first term and ending with 0 in the last term. Also, the

index of b increases by unity, starting with 0 in the first term and ending with n in the
last term.
In every term of the expansion, the sum of the indices of a and b is n.
In the binomial expansion of (a + b)
n
, taking a = x and b = y, we have
| |
1 2 2 3 3
0 1 2 3
1 2 2 3 3
0 1 2 3
( ) ( )
C C ( ) C ( ) C ( ) ... C ( )
Thus,
( ) C C C C ... ( 1) C
n
n
n n n n n n n n n n
n
n n n n n n n n n n n n
n
x y x y
x x y x y x y y
x y x x y x y x y y

= +
= + + + + +
= + + +

Example 1: Expand the expression (2x 5)
5

Solution:
By using the binomial theorem, we have
5 5 5 5 4 5 3 2 5 2 3 5 4 5 5
0 1 2 3 4 5
5 4 3 2
5 4 3 2
(2 5) C (2 ) C (2 ) (5) C (2 ) (5) C (2 ) (5) C (2 )(5) C (5)
(2 ) 5(16 )(5) 10(8 )(25) 10(4 )(125) 5(2 )(625) 3125
32 400 2000 5000 6250 3125
x x x x x x
x x x x x
x x x x x
= + +
= + +
= + +

The (r + 1)
th
term (denoted by T
r + 1
) is known as the general term of the expansion (a + b)
n

and it is given by
1
C
n n r r
r r
T a b

+
=

Example: The general term in the expansion of (5x 7y)
9
is given by
( ) ( ) ( ) ( ) ( )
9 9
9 9
1
C 5 7 1 C 5 7
r r r r r
r r r
T x y x y

+
= =
Middle term in the expansion of (a + b)
n
:
If n is even, then the number of terms in the expansion will be n + 1. Since n is even, n
+ 1 is odd. Therefore, the middle term is
th
1
2
n | |
+
|
\ .
term.
If n is odd, then n + 1 is even. So, there will be two middle terms in the expansion.
They are
th
1
2
n + | |
|
\ .
term and
th
1
1
2
n + | |
+
|
\ .
term.
In the expansion of
2
1
n
x
x
| |
+
|
\ .
, where x 0, the middle term is
th
2
1
2
n | |
+
|
\ .
, i.e., (n + 1)
th

term [since 2n is even].
It is given by
2 2
1
C C ,
n
n n n
n n
x
x
| |
=
|
\ .
which is a constant.
This term is called the term independent of x or the constant term.

Note: In the expansion of (a + b)
n
, r
th
term from the end = (n r +2)
th
term from the
beginning.

Example 2: In the expansion of
4
3
12
4
x
x
| |

|
\ .
, find the middle term and find the term which
is independent of x.

Solution:
As 4 is even, the middle term in the expansion of
4
3
12
4
x
x
| |

|
\ .
is the
th
4
1
2
| |
+
|
\ .
term, i.e., 3
rd

term, which is given by
2
2
3 6
4 2
3 2 1 2 2
12 144
C 6 54
4 16
x x
T T x
x x
+
| | | |
= = = =
| |
\ .
\ .

Now, we will find the term in the expansion which is independent of x. Suppose (r + 1)
th

term is independent of x.
The (r + 1)
th
term in the expansion of (a + b)
n
is given by
1
C
n n r r
r r
T a b

+
=
Hence, the (r + 1)
th
term in the expansion of
4
3
12
4
x
x
| |

|
\ .

is given by
( )
4
3
4
1
4
3 4
4
4
4 12 4
12
C
4
1 ( )
( 1) C 12
4
1
( 1) C (12) ( )
4
r
r
r r
r
r
r
r
r r
r
r r r
r
x
T
x
x
x
x

| | | |
=
| |
\ .
\ .
| |
=
|
\ .
| |
=
|
\ .

Now, a term will be independent of x if the index of x is zero, i.e., 12 4r = 0 r = 3.
Thus, the 4
th
term of the expansion is independent of x and is given by
4 3
3 4 3 3 3
4 3 1 3
1 1
( 1) C (12) 4 (12) (12) 1728
4 4
T T

+
| |
= = = = =
|
\ .